Vertical fluxes of nitrate in the seasonal nitracline of the Atlantic sector of the Arctic Ocean. Issue 7 (31st July 2016) - Randelhoff, Achim; Fer, Ilker; Sundfjord, Arild; Tremblay, Jean‐Éric; Reigstad, Marit
Abstract: This study compiles colocated oceanic observations of high‐resolution vertical profiles of nitrate concentration and turbulent microstructure around the Svalbard shelf slope, covering both the permanently ice‐free Fram Strait and the pack ice north of Svalbard. The authors present an overview over the seasonal evolution of the distribution of nitrate and its relation to upper ocean stratification. The average upward turbulent diffusive nitrate flux across the seasonal nitracline during the Arctic summer season is derived, with average values of 0.3 and 0.7 mmol m −2 d −1 for stations with and without ice cover, respectively. The increase under ice‐free conditions is attributed to different patterns of stratification under sea ice versus open water. The nitrate flux obtained from microstructure measurements lacked a seasonal signal. However, bottle incubations indicate that August nitrate uptake was reduced by more than an order of magnitude relative to the May values. It remains inconclusive whether the new production was limited by an unidentified factor other than N O 3 − supply in late summer, or the uptake was underestimated by the incubation method. Key Points: The nitrate drawdown in the photic zone is empirically strongly related to the development of seasonal stratification from ice melt Upward turbulent nitrate fluxes across the seasonal nitracline are small compared to estimates of annual nitrate drawdown on the shelves Under a future seasonal Arctic ice cover, increases in seasonal nitrate fluxes can be significant in the deep Eurasian Basin